IoT-Enabled Portable Water Quality Monitoring System - Chowdhury, Sumit Singha; R., Champaka K.; K., Ramesh Adiga (Journal of ISMAC, 2025)
Clean and safe drinking water is what we all depend on every day. With so many varieties of bottled water available stored in plastic, glass, copper, or even steel containers it's hard to tell whether the drinking water is safe. Most people have no idea that the type of bottle and storing it will actually determine water quality. For example, plastic bottles, when exposed to heat, are able to contaminate water with toxic chemicals, and prolonged use can lead to health issues. Copper bottles are widely utilized because of their health benefits, but if water stays in them for a long time, they are able to alter water pH and cause copper leaching. Glass bottles are normally safe but can easily get contaminated if not properly cleaned. To help people understand what they are drinking better, we developed a smart water quality tester using an Arduino UNO. It uses four sensors pH, TDS (Total Dissolved Solids), turbidity, and temperature to check if the water is clean and safe. Whether it is bottled mineral water, boiling tap water, or rainwater, this tester can analyze them all. The sensor readings are shown in real-time on a web dashboard. It's a simple and affordable method for testing water in our home, stores in shopping malls, or even in water bottling plants. This project aims to make individuals more aware of what is in their water and how the bottles they consume from can help bring about a change. It is a step towards making water safety more accessible, clear, and trustworthy for everyone.
Keywords: Arduino UNO; Drinking Water Safety; pH Sensor; TDS Sensor; Turbidity Sensor; DS18B20 Temperature Sensor; Portable Water Analysis